2007
DOI: 10.2169/internalmedicine.46.6191
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Mastopathy of Bilateral Breasts in an Elderly Japanese Woman with Type 2 Diabetes: A Case Report and a Review of the Literature in Japan

Abstract: We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
1
4
0
1
Order By: Relevance
“…In most series, the patients are relatively young (premenopausal age), and have an early onset of long-standing type 1 diabetes, generally with severe diabetic complications. Occasionally, the condition has also been observed in patients with type 2 diabetes [10,11] or those with autoimmune disorders such as Hashimoto's thyroiditis, arthropathy, and lupus erythematosus [1,6]. Epithelioid fibroblasts, believed to be specific for diabetic condition, were seen in our case without a diabetic history and other clinical data.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In most series, the patients are relatively young (premenopausal age), and have an early onset of long-standing type 1 diabetes, generally with severe diabetic complications. Occasionally, the condition has also been observed in patients with type 2 diabetes [10,11] or those with autoimmune disorders such as Hashimoto's thyroiditis, arthropathy, and lupus erythematosus [1,6]. Epithelioid fibroblasts, believed to be specific for diabetic condition, were seen in our case without a diabetic history and other clinical data.…”
Section: Discussionsupporting
confidence: 48%
“…Thus, epithelioid fibroblasts appear to be not as specific as previously maintained in the diabetic mastopathy. Although many possible mechanisms have been suggested for the cause of lymphocytic mastopathy, none has been proven [5,11]. While some of the discussed reasons may explain the findings in a setting of hyperglycemia and exogenous insulin use, an autoimmune basis would best address their presence among nondiabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…This is fitting with our patient who had a 23-year history of reasonably well-controlled diabetes complicated by minimal retinopathy. To a much lesser extent, diabetic mastopathy has been reported in men [4] and in patients with Type II diabetes who are often insulin dependent [5, 6]. Clinical features include unilateral or bilateral, single or multiple, nontender, palpable breast masses that are firm to hard in consistency, mimicking malignancy, and mandating further evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…This condition is also found in patients with other endocrine disorders, especially thyroid diseases 2,6,8) . Honda et al 10) reported differences of diabetic mastopathy between Japan and Western countries, showing that most cases in Western countries are in premenopausal women with type I diabetes, while in Japan, most cases are in postmenopausal women with type II diabetes. They speculated that differences of genetic factors, including HLA type, between Japan and the Western countries were the source of this finding.…”
Section: Case Reportmentioning
confidence: 99%